Lifestyle Modifications and Nutraceutical Interventions in the Prevention and Management of Metabolic Syndrome - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2025)
Abdominal obesity, dyslipidemia, hypertension, and hyperglycemia are metabolic risk factors that are grouped together to define metabolic syndrome (MetS). It is now widely recognized that MetS is linked to a higher risk of type 2 diabetes (T2DM) and cardiovascular disease (CVD). Overall, the pathophysiology of MetS initiated by the imbalance of nutrition intake and physical activity. It involves a complex interplay of insulin resistance (IR), inflammation, dysregulated adipocyte function, and genetic susceptibility, all of which contribute to the metabolic dysfunction. Lifestyle modifications play a crucial role in managing and preventing MetS. Key strategies include adopting a balanced diet like Mediterranean diet, Dietary Approaches to Stop Hypertension (DASH), or caloric restriction (CR), engaging in regular physical activity, and maintaining a healthy weight. Nutraceuticals, including polyphenols and CR-mimetic agents, improve insulin sensitivity, reduce inflammation, lower blood pressure and cholesterol levels, reducing oxidative stress, and promoting autophagy. In addition to lifestyle changes, drug therapy may be necessary for some individuals to manage specific risk factors, such as diuretics, angiotensin-converting enzyme (ACE) inhibitors, angiotensin II receptor blockers (ARB), calcium channel blockers, and beta blockers for hypertension; biguanides, sulfonylureas, dipeptidyl peptidase-4 (DPP-4) inhibitors, glucagon-like peptide 1(GLP-1) receptor agonists, sodium-glucose co-transporter 2 (SGLT2) inhibitors, and thiazolidinediones for hyperglycemia; and statins for dyslipidemia. Early diagnosis, including waist circumference and blood pressure measurement, serum cholesterol and glucose testing, and intervention, is essential to effectively manage MetS and prevent the progression of associated diseases. In conclusion, understanding the risk factors and associated risks of MetS, along with the implementation of lifestyle modifications such as dietary and nutraceutical interventions including polyphenols and CR-mimetic agents, is vital for reducing the burden of this syndrome. Early diagnosis and proactive management are key to improving long-term health outcomes.KEYWORDS: metabolic syndrome, abdominal obesity, insulin resistance, diet, nutraceuticals